Is the Gold Standard in Medical Clinical Trials Really Golden? An Opinion - Doepp, Manfred (British Journal of Healthcare and Medical Research, 2025)
The randomized placebo-controlled peer-reviewed double-blind study: Randomized Controlled Trial (RCT) is the gold standard. Theoretically, this is correct. However, in reality, there are a number of false studies on the « marquet » in the scientific community. This is primarily due to human shortcomings, namely the investigator’s dependence on their client and the client’s financial interests. Billions in future sales are often at stake, whereas the physician receives a small salary and is dependent on subsidies from the initiator. It’s also about the problem of “publish or perish.” This article examines whether there are alternative ways to improve this unacceptable situation.